Information support for the procedure of providing land plots for investment projects - Gura Dmitry; Khusht Nafset; Popova Olga; Markovsky Ivan; Pshidatok Saida (E3S Web of Conferences, 2020)
Nowadays, the problem of integrated and sustainable development of territories is especially acute in view of the fact that the process of urbanization is growing every year. A special role in implementing programs for improving the state of the urban environment and social spheres is played by investment projects, which are economic or social projects that are based on investments. At the same time, the implementation of most of these measures requires the assistance of state authorities or local self-government, which consists mainly in the provision of land for planned investment objects, for which a special order is used. This paper is devoted to issues related to the procedure for the provision of land plots for the implementation of investment projects in the territory of the constituent entity of the Russian Federation - Krasnodar Territory. The legal and regulatory framework governing the implementation of this procedure is analyzed, the existing information support offered to potential investors is considered. Conclusions are made about the main shortcomings of information support, a solution to the identified problem is proposed by creating an investment-oriented information system.